“I don't even have time to exist”: the everyday life of university teachers - Diego Barragan; Magda Sarat (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2025)
This paper research how teachers deal with difficulties encountered in the everyday workplace. A qualitative approach was used; interviews with professors, both full and part-time, and participant observation in public and private universities in Brazil and Colombia. Three aspects were proposed to understand how they deal with difficulties: efforts, relationships and perspectives. Efforts refer to the intensity of activities, the responsibilities they must assume and the changes they must face in their work. The relationships, which stand out, are with those who share their day-to-day life with others (children, partners, parents, friends or colleagues). Finally, the views of their own labours stand out, highlighting a strong affective engagement  experienced by teachers as members of a community. The complexity of their activities, added to the intensity of their role, makes them permanently look for solutions to deal with difficulties, leading them to establish in their teaching duties as the core of their lives.